Interfacial Residual Stress Relaxation in Perovskite Solar Cells with Improved Stability. Issue 48 (16th October 2019) - Wang, Hao; Zhu, Cheng; Liu, Lang; Ma, Sai; Liu, Pengfei; Wu, Jiafeng; Shi, Congbo; Du, Qin; Hao, Yanmin; Xiang, Sisi; Chen, Haining; Chen, Pengwan; et al.
Abstract: To improve the photovoltaic performance (both efficiency and stability) in hybrid organic–inorganic halide perovskite solar cells, perovskite lattice distortion is investigated with regards to residual stress (and strain) in the polycrystalline thin films. It is revealed that residual stress is concentrated at the surface of the as‐prepared film, and an efficient method is further developed to release this interfacial stress by A site cation alloying. This results in lattice reconstruction at the surface of polycrystalline thin films, which in turn results in low elastic modulus. Thus, a "bone‐joint" configuration is constructed within the interface between the absorber and the carrier transport layer, which improves device performance substantially. The resultant photovoltaic devices exhibit an efficiency of 21.48% with good humidity stability and improved resistance against thermal cycling. Abstract : The elastic modulus of 3D perovskite is very close to that of human bones and the elastic modulus of 2D perovskite with long chains is close to that of cartilage. By reconstructing a crystal lattice with different A cations at the surface of perovskite films, a nature "bone‐joint" configuration is built in perovskite, which provides a cushioning effect to external stresses.